(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
After gaining independence, the revival of our national heritage made it possible to objectively study the history of Kokand papermaking produced during the Kokand historical period. As we know, the emergence of papermaking in Kokand has its own historical conditions. Due to the political crisis and turmoil that occurred in the Central Asian states in the 18th and 19th centuries, the entire cultural life of Central Asia and its specific part, papermaking, fell into decline. This is also evidenced by the fact that the samples of paper created during this period absolutely do not reach the quality of the papers produced in previous periods.